ANALYSIS OF HOSPITALITY&TOURISM INDUSTRY TRENDS IN SOUTHERN-WESTERN EUROPE, BETWEEN THE INTERNATIONAL ORGANIZATIONS' ESTIMATES FOR 2020 - Gabriela Stanciulescu; Vergil Voineagu; Emilia Titan; Simona Ghita; Cristina Boboc (European Regional Science Association (ERSA), 2010)
Europe will remain the most visited touristic destination in the world with a total of 717 million tourists in 2020. The foreseen increase rate is 3.1% per year. This is one point lower than the world average, leading to a loss of market quota of Europe from almost 60% in 1995 to 46% in 2020. This paper presents the features of Southern-Western European tourism in 2020. The paper analyses the European touristic level according to the tourist arrivals in the Southern and Western Europe, as well as to the money collections. It has been foreseen that the number of tourist international arrivals will increase reaching to almost 1.6 billion in 2020 (25 times more comparing to the value registered at the end of 1990). Collections from international tourism are to reach 2,000 billion USD until 2020. The empirical results of the research will demonstrate the evolutions and tendencies of S-W European tourism. In case the dynamics of the European tourism will remain the same in the future, as the experts of OMT/UNWTO anticipate, it is necessary for stimulation measures to be adopted, as well as measures of supporting the tourism industry.
Keywords: 330; European tourism; international tourist arrivals; Gross Domestic Product